2014
DOI: 10.2174/1570162x12666140526114956
|View full text |Cite
|
Sign up to set email alerts
|

Brain Inflammation is a Common Feature of HIV-Infected Patients without HIV Encephalitis or Productive Brain Infection

Abstract: HIV-associated neurocognitive disorders (HAND) describes different levels of neurocognitive impairment, which are a common complication of HIV infection. The most severe of these, HIV-associated dementia (HIV D), has decreased in incidence since the introduction of combination antiretroviral therapy (cART), while an increase in the less severe, minor neurocognitive disorder (MND), is now seen. The neuropathogenesis of HAND is not completely understood, however macrophages (MΦ)s/microglia are believed to play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
112
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 22 publications
6
112
0
2
Order By: Relevance
“…Recently, we reported prominent neuroinflammation in brains of HIV infected subjects without encephalitis or productive infection that is similar but less severe than that seen in HIVE (Tavazzi et al, 2014). It is possible that the decrease in M-CSF we observe in SIV brain is due to increased secretion of the protein by astrocytes and/or microglia in response to chronic inflammation, even in the absence of gross pathological alterations or productive virus.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Recently, we reported prominent neuroinflammation in brains of HIV infected subjects without encephalitis or productive infection that is similar but less severe than that seen in HIVE (Tavazzi et al, 2014). It is possible that the decrease in M-CSF we observe in SIV brain is due to increased secretion of the protein by astrocytes and/or microglia in response to chronic inflammation, even in the absence of gross pathological alterations or productive virus.…”
Section: Discussionmentioning
confidence: 81%
“…This supports the notion of a spatial relationship between the two cytokines (Wei et al, 2010), where IL-34 expression and function is limited to specific tissues (Wang et al, 2012) and M-CSF plays a larger role in the skeletal and hematopoietic systems. Accordingly, M-CSF, which is normally detected in plasma, may contribute to the increased frequency of circulating CD16 + CD163 + monocytes in viremic HIV infected subjects reported by ourselves and others (Allen et al, 1991, Locher et al, 1994, Thieblemont et al, 1995, Fischer-Smith et al, 2008b), as M-CSF increases the frequency of this subset in vitro , while IL-34 contributes more to microglial activation and CD16/CD163 expression in HIV brain (Fischer-Smith et al, 2001, Tavazzi et al, 2014). M-CSF may also support the significant accumulation of CD16 + /CD163 + MΦs from the peripheral blood in HIVE/SIVE brain that serves as the principle reservoir of productive virus in the CNS (Fischer-Smith et al, 2001, Fischer-Smith et al, 2008a).…”
Section: Discussionmentioning
confidence: 87%
“…The presence of viral DNA ([20] but absence of viral RNA and p24 protein [24] in astrocytes in HIV-1-infected patients’ post-mortem brain tissues has been suggested as latent viral infection, but the significance of these findings is unknown. Thus, to investigate further the latent HIV-1 infection in primary astrocytes, a robust infection model of VSV-pseudotyped HIV-1 infected astrocytes was used ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular investigations of HIV-1-infected brain tissues from post-mortem cases have demonstrated that viral DNA in 3% to 19% of astrocytes is an unproductive infection [15-23]. Recently, immunohistochemical study of brain sections from individuals with HIV-associated neurocognitive disorders found that productive HIV-1 infection was undetectable [24]. Some studies, however, have shown that HIV-1 infection in astrocytes is moderately productive [12, 25-28].…”
Section: Introductionmentioning
confidence: 99%
“…O HIV pode permanecer latente no SNC por muitos anos e sua presença pode levar a déficits sutis no funcionamento cognitivo, independente da supressão de HIV-RNA no sangue (18) . Esta independência da presença do vírus entre o plasma sanguíneo e o SNC pode ser resultado da má distribuição dos antirretrovirais no SNC.…”
Section: Revisão De Literatura a Hiv E Sistema Nervoso Centralunclassified